Photochemical pump and NMR probe to monitor the formation and kinetics of hyperpolarized metal dihydrides. Issue 12 (16th August 2016) - Procacci, Barbara; Aguiar, Pedro M.; Halse, Meghan E.; Perutz, Robin N.; Duckett, Simon B.
Abstract : Pulsed-laser experiments validate photochemical pump-NMR probe spectroscopy for monitoring the rate of rapid H2 oxidative addition to a metal centre. Abstract : On reaction of IrI(CO)(PPh3 )2 1 with para-hydrogen ( p -H2 ), Ir(H)2 I(CO)(PPh3 )2 2 is formed which exhibits strongly enhanced 1 H NMR signals for its hydride resonances. Complex2 also shows similar enhancement of its NMR spectra when it is irradiated under p -H2 . We report the use of this photochemical reactivity to measure the kinetics of H2 addition by laser-synchronized reactions in conjunction with NMR. The single laser pulse promotes the reductive elimination of H2 from Ir(H)2 I(CO)(PPh3 )2 2 in C6 D6 solution to form the 16-electron precursor1, back reaction with p -H2 then reforms2 in a well-defined nuclear spin-state. The build up of this product can be followed by incrementing a precisely controlled delay ( τ ), in millisecond steps, between the laser and the NMR pulse. The resulting signal vs. time profile shows a dependence on p -H2 pressure. The plot of k obs against p -H2 pressure is linear and yields the second order rate constant, k 2, for H2 addition to1 of (3.26 ± 0.42) × 10 2 M −1 s −1 . Validation was achieved by transient-UV-vis absorption spectroscopy which gives k 2 of (3.06 ± 0.40) × 10 2 M −1 s −1 . Furthermore, irradiation of a C6 D6 solution of2 with multiple laser shots, in conjunction with p -H2 derived hyperpolarization, allows the detection and characterisation of two minor reaction products, 2a and3, which are produced in such low yields that they are not detected without hyperpolarization. Complex2a is a configurational isomer of2, while3 is formed by substitution of CO by PPh3 .